The British world : diaspora, culture, and identity - Bridge, Carl; Fedorowich, Kent, 1959- (F. Cass, 2003)
This collection of essays is based upon the assumption that the British Empire was held together not merely by ties of trade and defence, but by a shared sense of British identity that linked British communities around the globe.